BRIDGING THE THEORY-PRACTICE GAP IN ART EDUCATION: A STRUCTURED PEDAGOGICAL MODEL FOR CRITICAL AND CREATIVE APPLICATION: BRIDGING THE THEORY-PRACTICE GAP IN ART EDUCATION: A STRUCTURED PEDAGOGICAL MODEL FOR CRITICAL AND CREATIVE APPLICATION - Alfarisi, Salman; Nursilah, Nursilah (International Journal of Performing Arts (IJPA), 2025)
Higher art education emphasizes theoretical mastery as a crucial foundation, yet many studentsstruggle to apply this knowledge in both criticism and creation. The persistent gap between 'knowing'and 'doing' remains a critical challenge in art pedagogy, often hindering learning outcomes. Thisarticle proposes a structured pedagogical model designed to bridge this divide. By synthesizingScaffolding Theory and Situated Learning Theory, the model presents a systematic four-stepframework: (1) theoretical deconstruction for deep comprehension, (2) methodological bridgingbetween theory and artistic objects, (3) dialogic operationalization through analytical frameworks,and (4) simulation and analytical design. This model is demonstrated through a case study applyingHomi K. Bhabha’s Cultural Hybridity Theory to Lenong Betawi, a traditional Indonesianperformance art. The proposed framework offers practical guidance for art educators to transformstudents’ passive theoretical knowledge into active analytical and creative competence. Itcontributes to the field of art pedagogy by integrating established educational theories into acoherent, actionable strategy for teaching theory application in art practice